1981
DOI: 10.1007/bf01948381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of catalase, peroxidase, superoxide dismutase and 10 scavengers of oxygen radicals in carrageenin edema and in adjuvant arthritis of rats

Abstract: Catalase, peroxidase and superoxide dismutase were found to inhibit significantly carrageenin edema and the primary phase of adjuvant arthritis in rats after i.v. injection. Heat-inactivated enzymes were as effective as the native enzymes. None of 10 scavengers of oxygen radicals inhibited the adjuvant arthritis at any time. Accordingly, no evidence for a participation of oxygen radicals in the secondary arthritis phase could be found, whereas a role of oxygen radicals in the primary arthritis phase and in car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…18,19 Several inflammatory mediators like complement, histamine, kinins, prostaglandins and pro-inflammatory cytokines have been suggested to play a role in the mechanism of inflammation. [20][21] Edema, which develops after egg albumin injection, is a biphasic event. The initial phase is attributed to the release of histamine and serotonin and lasting up to 2 h. While the later phase, occurring from 3 to 5 h after the injection of the irritant is induced by bradykinin, protease, prostaglandins and lysosome.…”
mentioning
confidence: 99%
“…18,19 Several inflammatory mediators like complement, histamine, kinins, prostaglandins and pro-inflammatory cytokines have been suggested to play a role in the mechanism of inflammation. [20][21] Edema, which develops after egg albumin injection, is a biphasic event. The initial phase is attributed to the release of histamine and serotonin and lasting up to 2 h. While the later phase, occurring from 3 to 5 h after the injection of the irritant is induced by bradykinin, protease, prostaglandins and lysosome.…”
mentioning
confidence: 99%
“…The mechanisms of the suppressive action could be direct, by elimination of potentially toxic agents as superoxide and hydrogen peroxide, or indirect, by prevention of the formation of hydroxyl radicals and lipid peroxides. Although several investigators independently demonstrated the effects of scavenging enzymes in different models of experimental inflammation, other data cast some doubt on the general validity of these findings (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…No significant change was seen in the post treated group. Evidence exists that SOD were found to inhibit the primary phase of the adjuvant arthritis but had no effect on the secondary phase of adjuvant arthritis (26). This shows that when Type II colragen is given after the onset of the disease, it has no role on the activity of superoxide dismutase.…”
Section: Discussionmentioning
confidence: 98%